Factors influencing the performance of rapid SARS‐CoV‐2 antigen tests under field condition. Issue 2 (23rd December 2021) - Begum, Mst. Noorjahan; Jubair, Mohammad; Nahar, Kamrun; Rahman, Sezanur; Talha, Muhammad; Sarker, Md Safiullah; Uddin, A K M Nasir; Khaled, Saifuddin; Uddin, Mohammed Shehab; Li, Zhibiao; Ke, Tianlin; Rahman, Mohammed Ziaur; et al.
Abstract: Background: Globally, real‐time reverse transcription–polymerase chain reaction (rRT‐PCR) is the reference detection technique for SARS‐CoV‐2, which is expensive, time consuming, and requires trained laboratory personnel. Thus, a cost‐effective, rapid antigen test is urgently needed. This study evaluated the performance of the rapid antigen tests (RATs) for SARS‐CoV‐2 compared with rRT‐PCR, considering different influencing factors. Methods: We enrolled a total of 214 symptomatic individuals with known COVID‐19 status using rRT‐PCR. We collected and tested paired nasopharyngeal (NP) and nasal swab (NS) specimens (collected from same individual) using rRT‐PCR and RATs (InTec and SD Biosensor). We assessed the performance of RATs considering specimen types, viral load, the onset of symptoms, and presenting symptoms. Results: We included 214 paired specimens (112 NP and 100 NS SARS‐CoV‐2 rRT‐PCR positive) to the analysis. For NP specimens, the average sensitivity, specificity, and accuracy of the RATs were 87.5%, 98.6%, and 92.8%, respectively, when compared with rRT‐PCR. While for NS, the overall kit performance was slightly lower than that of NP (sensitivity 79.0%, specificity 96.1%, and accuracy 88.3%). We observed a progressive decline in the performance of RATs with increased Ct values (decreased viral load). Moreover, the RAT sensitivity using NP specimens decreased over the time of the onset of symptoms. Conclusion: The RATs showed strong performance under field conditions and fulfilled the minimum performance limit for rapid antigen detection kits recommended by World Health Organization. The best performance of the RATs can be achieved within the first week of the onset of symptoms with high viral load. Abstract : In this study, we aimed to evaluate the performance of rapid antigen tests (RATs) considering factors, ie, specimen types, viral RNA copy number, the onset of symptoms, and presenting symptoms. A total of 214 symptomatic individuals with known COVID‐19 status were enrolled, and paired NP and NS specimens were collected. RAT (InTec and SD Biosensor) results were compared with rRT‐PCR results. For NP specimens, the average sensitivity, specificity, and accuracy of the RATs were 87.5%, 98.6%, and 92.8%, respectively; for NS, the sensitivity was 79.0%, the specificity was 96.1%, and the accuracy was 88.3%. We observed a progressive decline in the performance of RATs with increased Ct values (decreased viral RNA copy number). Moreover, the RAT sensitivity decreased over the onset of symptoms using NP. The RATs showed strong performance under field conditions within the first week of the onset of symptoms with high viral RNA copies.